Entity Framework 4.0 Recipes - Tenny, Larry (Apress, 2012)
This book is for anyone who develops applications for the Microsoft platform. All of us who work in this field need access to data in our applications. We are all interested in more powerful and intuitive ways to reason about and program against the real-world objects in our applications. It makes much more sense for us to architect, design, and build applications in terms of customers, orders, and products rather than rows and columns scattered among tables locked away in a database. Because we can reason about problem space in terms of real-world objects, we have a lotmore confidence in our design and in the code that we build. We are also better able to document and explain our applications to others. This makes our code much more maintainable. Entity Framework is not just for developers. Microsoft is aggressively positioning the modeling concepts in Entity Framework to serve as the conceptual domain for Reporting Services and Integration Services as well as other technologies that process, report on, and transform data. Entity Framework is quickly becoming a core data access foundation for many other Microsoft technologies. This book contains well over 150 recipes that you can put to work right away. Entity Framework is a large and complex topic. Perhaps it’s too big for a monolithic reference book. In this book, you will find direct and self-contained answers to just about any problem you’re facing in building your Entity Framework-powered applications. Along the way, you’ll learn an enormous amount about Entity Framework.